Influence of polymorphisms of the beta-2 adrenergic receptor on the presence of exercise-induced bronchospasm in adolescents - Consentino,Cássio Leandro Mühe (2016)
Abstract Objective: To determine the influence of polymorphisms of the beta-2 adrenergic receptor (ADRB2) in triggering exercise-induced bronchospasm (EIB) in adolescents. Methods: The subjects were divided into two groups: present EIB (EIB+) (n=45) and absent EIB (EIB−) (n=115). The bronchial provocation test with exercise was performed with a protocol that consisted of walking/running for at least eight minutes at high intensity, i.e., >85% of maximum heart rate, considering EIB+ as a 10% decrease in forced expiratory volume in one second (FEV1). The genotyping of the ADRB2 gene was performed by the Taqman method, using the Step One Plus system. Independent t-test, Mann–Whitney and Chi-square tests, as well as Spearman's correlation coefficient were used for the statistical analysis. Results: Age, body weight, height, FEV1, FVC and FEV1/FVC ratio were lower in the EIB+ group when compared to EIB− (p<0.05). There were no significant differences in the proportion of the allele at position 27 and Arg16Gly and Gln27Glu genotypes between the EIB+ and EIB− groups (p=0.26; p=0.97 and p=0.43, respectively). However, there was a trend toward statistical significance regarding the greater proportion of the Gly16 allele for the EIB+ when compared to the EIB− group (p=0.08). Conclusions: The presence of polymorphisms associated with the Glu27 allele and Arg16Gly and Gln27Glu genotypes had no influence on EIB. However, the statistical trend toward greater frequency of the Gly16 allele in individuals with EIB+ can be considered evidence of the influence of polymorphisms of the ADBR2 gene on EIB in adolescents.